Color‐Tunable Dual‐Mode Organic Afterglow from Classical Aggregation‐Caused Quenching Compounds for White‐Light‐Manipulated Anti‐Counterfeiting. Issue 7 (12th January 2023) - Liang, Yaohui; Xu, Chao; Zhang, Huaqing; Wu, Shiying; Li, Jian‐An; Yang, Yifan; Mao, Zhu; Luo, Suilian; Liu, Cong; Shi, Guang; Sun, Fengqiang; Chi, Zhenguo; et al.
Abstract: Color‐tunable dual‐mode organic afterglow excited by ultraviolet (UV) and white light was achieved from classical aggregation‐caused quenching compounds for the first time. Specifically, two luminescent systems, which could produce significant organic afterglow composed of persistent thermally activated delayed fluorescence and ultralong organic phosphorescence under ambient conditions, were constructed by doping fluorescein sodium and calcein sodium into aluminum sulfate. Their lifetimes surpassed 600 ms, and the dopant concentrations were as low as 5×10 −6 wt %. Moreover, the persistent luminescence colors of the materials could be tuned from blue to green and then to yellow by simply varying the concentrations of guest compounds or the temperature in the range of 260–340 K. Inspired by these exciting results, the afterglow materials were used for UV‐ and white‐light‐manipulated anti‐counterfeiting and preparation of elastomers with different colors of persistent luminescence. Abstract : Luminescent materials with dual‐mode organic afterglow composed of persistent thermally activated delayed fluorescence and ultralong organic phosphorescence were developed by doping fluorescein sodium and calcein sodium into aluminum sulfate, respectively. It is found that their afterglow can be excited by ultraviolet and white light, and the persistent luminescence colors can be tuned by varying temperatures and dopant concentrations.